2014
DOI: 10.15288/jsad.2014.75.241
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does One More Drink Matter? Examining Effects of Event-Level Alcohol Use and Previous Sexual Victimization on Sex-Related Consequences

Abstract: ABSTRACT. Objective:The fi rst semester of college has been associated with increased drinking and sexual risk. However, it remains unclear why some drinking occasions result in experiencing negative sexual consequences whereas others do not. The current study used a diary-based approach to assess the event-level effect of alcohol use and previous adult/adolescent sexual victimization (PSV) on experiencing negative sex-related consequences in fi rst-year college women. Method: Participants (N = 120) provided r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
4
19
1
Order By: Relevance
“…One event‐level study on the effects of drinking during a sexual event found an important within‐person association, such that each drink consumed above one's “mean” alcohol consumption was associated with a 13% increase in the likelihood of reporting unprotected sex, regretted sex or unwanted sexual attention (Scaglione et al. ).…”
Section: The Role Of Alcoholmentioning
confidence: 99%
See 3 more Smart Citations
“…One event‐level study on the effects of drinking during a sexual event found an important within‐person association, such that each drink consumed above one's “mean” alcohol consumption was associated with a 13% increase in the likelihood of reporting unprotected sex, regretted sex or unwanted sexual attention (Scaglione et al. ).…”
Section: The Role Of Alcoholmentioning
confidence: 99%
“…The authors concluded that women who regularly drink heavily are more likely to be in situations that may afford the opportunity for sexual assault. One event-level study on the effects of drinking during a sexual event found an important within-person association, such that each drink consumed above one's "mean" alcohol consumption was associated with a 13% increase in the likelihood of reporting unprotected sex, regretted sex or unwanted sexual attention (Scaglione et al 2014).…”
Section: The Role Of Alcoholmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative alcohol use consequences increase linearly with increased alcohol consumption and can even occur from small amounts of alcohol use (Barnett et al, 2014). Each individual drink increases risk of negative alcohol consequences, as much as a 13% increase in likelihood of negative consequences per drink (Scaglione et al, 2014).…”
Section: Methodological Concernsmentioning
confidence: 99%